Evaluación del desempeño laboral aplicado a los colaboradores de ORVISA en la sucursal Bagua Grande y sus beneficios en el año 2013 - Ayala Linares, Mercedes del Carmen (2014)
Human Resources Management also called Human Resource Management (HRM), involves the development of different types of processes that lead to achieving the objectives of the organization and ensure proper management of human resources. One of these processes is the Performance Assessment, which seeks to determine the employee's performance in office and if it detects weaknesses implement improvement plans. Its importance is that it is one of the processes most influence in decision-making for staff, for that reason should be applied with respect to each of its steps and trained people previously established techniques. This research is framed in the company Orvisa, Bagua Grande branch it is a commercial private institution, located in the city of Bagua Grande Amazonas department. The purpose of the research was to analyze Process Performance Evaluation Applied to Administrative Staff of the institution, through a descriptive study design field, and a population that was represented by 20 employees, who provided the information required by a questionnaire with the help of an interview to collect the necessary data on the implementation of the process. Once the data studied was determined that there are a variety of weaknesses in the process that prevents proper implementation.